Representation of Women as Subaltern in Girls of Paper and Fire by Natasha Ngan - Randi Ramadhan (Morphosis: Journal of Literature, 2024)
This study is entitled “Representation of Women as Subaltern in Girls of Paper and Fire Novel”. This study aims to analyzed subalterns are portrayed in the novel Girls of Paper and Fire and to analyzed impact of subaltern describe in the novel Girls of Paper and Fire. The object of the study is a novel, this study is attempted with a qualitative method to reveal the problems and the impact that occurs in the novel. This study applies the subaltern theory entitled Can the Subaltern Speak ? By Spivak (1985). The results of the study to find out subaltern in the novel Girls of Paper and Fire and to uncover the impact of subaltern in the women character in the novel Girls of Paper and Fire.. The impact that happens to the main character after becoming a subalternized person in this novel is related to his daily mental health, she is always feels in danger and Lei’s life is a terrible thing in his mind. Keywords: feminist, subaltern ,and women